PENERAPAN METODE THINK PAIR SHARE TERHADAP KEMAPUAN SISWA KELAS VII SMP NEGERI 14 SIGI MENULIS LAKON - Nasim Taha (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2023)
The problem in this study is the ability of students of SMP VII SMP Negeri 14 Sigi who are still very minimal in writing plays which results in a lack of understanding of the teacher in developing learning methods, and the purpose of this study is to describe or explain students' abilities in writing plays through the Think Phair Share method. , the type in this research is classroom action research with a quantitative description approach, in which the researcher goes directly to the class/school to collect data by means of direct observation techniques, interview techniques, and evaluation techniques, besides that this research method the researcher goes through the steps namely, place of research location, data collection techniques, and data analysis techniques. From the results of the research conducted, it can be seen that using the think pair share method can increase students' ability to write plays by up to 100%.